The severity of mobile phone addiction and its relationship with quality of life in Chinese university students - Li, Lu; Lok, Grace K.I.; Mei, Song Li; Cui, Xi Ling; Li, Lin; Ng, Chee H.; Ungvari, Gabor S.; Zhang, Juan; An, Feng Rong; Xiang, Yu Tao (PeerJ, 2020)
Objective This study examined the severity of mobile phone addiction and its relationship with quality of life (QOL) in Chinese university students. Methods A total of 2,312 university students from Macao, Hong Kong and mainland China participated in this cross-sectional study. The Mobile Phone Addiction Scale (MPAS), and the World Health Organization Quality of Life-Brief version (WHOQOL-BREF) rating instruments were used to assess the severity of mobile phone addiction and QOL, respectively. Results Compared to students in mainland China, those in Macao and Hong Kong were more likely to have excessive mobile phone use. Multiple linear regression revealed that high academic pressure and poor academic performance were positively associated, while male gender, greater interest in academic major and long sleep duration were negatively associated with the severity of mobile phone addiction. Students addicted to mobile phone use had significantly lower scores across all QOL domains. Conclusion Due to the adverse impact of excessive mobile phone use on QOL, public education and effective preventive measures should be developed for Chinese university students.
Keywords: Mobile phone use; Quality of life; University students; China